App-Based Investment Platform and Investment Decision Making: A Study of Retail Investor Behavior in Indonesia - Annisa Nuraini Tahir; Dwi Nastiti Danarsari (Green Publisher Indonesia, 2023)
The significant growth of retail investors in Indonesia between 2020 and 2022 is partly attributable to technological advancements that have made it easier to access investments through a variety of applications. Previous studies in developing nations like Indonesia, India, and Pakistan suggested that perception biases have influence on retail investor decision making. However, given the capabilities of current investing applications like the display of historical stock/mutual fund price data, retail investors should ideally be able to make more rational investment decisions. This study employs partial least square structural equation modeling (PLS-SEM) to examine the role of overconfidence, representativeness, and loss aversion biases that affect rational investment decision making. As an application feature, historical price data serves as the moderating variable of the interaction between them. The result of this study indicates that overconfidence influences rational investment decision making in a positive and significant manner, while representativeness and loss aversion do not have a significant effect. Price historical data as application feature also does not have significant effect in moderating the relationship between them.